Nonsuicidal Self‐Injury: Increased Prevalence in Engagement. Issue 6 (28th August 2017) - Wester, Kelly; Trepal, Heather; King, Kelly
Abstract : While some suggest nonsuicidal self‐injury (NSSI) is increasing, very little has been done systematically to explore this possibility. The current study employed three cohorts of freshman (total N  = 949) from the same university across a period of 7 years to explore engagement in NSSI. Related intrapersonal factors were also examined. NSSI lifetime and current engagement use drastically increased across the three cohorts. Anxiety followed a similar trajectory as NSSI behaviors as increasing in reported levels, while depression and coping behaviors did not. Implications of these trends are discussed.